The utilization of medicine plants as alternative for wound healing: a bibliographic analysis (Research, Society and Development, 2022)
Introduction: The use of medicinal plants grants prophylactic and curative properties, becoming recognized by the World Health Organization (WHO). This method has great benefits as it is cost-effective, in addition to being a non-invasive alternative. Objective: To analyze the benefits of medicinal plants for the treatment of wounds. Methods: This is an integrative literature review, carried out through the databases: SciVerse Scopus and Medical Literature Analysis and Retrievel System Online and through the databases: Nursing Database, Latin American and Caribbean Literature in Health Sciences and Spanish Bibliographic Index in Sciences and Health, indexed via the Virtual Health Library. Ten articles were included because they met the proposed objective. From the literature review and analysis of the studies indexed in the electronic platforms, 98 scientific studies were found, and only 33 studies were selected, 17 met the previously established inclusion criteria, of these, 07 were excluded based on the exclusion criteria, leaving 10 articles for study composition and analysis. Results: Studies show that medicinal plants have enormous healing potential, in addition to numerous other medicinal contributions, such as: greater collagen synthesis, greater amount of fibroblasts and angiogenesis (responsible for debridement and physiological remodeling). Final considerations: The study points out that it is necessary to implement integrative practices that promote knowledge about the possible plants that could participate in the treatment of the lesion, acting as a non-pharmacological method.